PENGEMBANGAN MODEL PjBL BERBANTUAN MEDIA DIGITAL PADLET UNTUK MENINGKATKAN LITERASI SAINS KELAS IV SDN SATRIYAN 03 - Savitri, Silvi Aprilia; Alfi, Cindya; Fatih, Mohammad (Cerdas Proklamator, 2024)
The following research aims to develop a Project Based Learning (PjBL) model assisted by Padlet digital media to increase the scientific literacy of fourth grade students at SDN Satriyan 03. This research adapts the Research and Development (R&D) type of research using the Borg and Gall model. Data was collected in the form of qualitative and quantitative data, including data from expert validation, data from product trial results, as well as data from students' scientific literacy test results. Data collection was carried out in interviews, observations, questionnaires and tests. The results of the research show that the PBL model assisted by Padlet digital media is valid and feasible for increasing the scientific literacy of fourth grade students at SDN Satriyan 03. Using the PBL model assisted by Padlet can help students understand scientific concepts, apply them and relate them to life